Setting off on the right path: make your research regulatory relevant - Anna Pohl; Elise Morel; Elise Morel; Eric A. J. Bleeker; Sean Kelly; Rachel Smith; Claus Svendsen; Thomas A. J. Kuhlbusch; Thomas A. J. Kuhlbusch; Thomas A. J. Kuhlbusch; Elisabeth Heunisch (Frontiers in Research Metrics and Analytics)
Scientifically well-established methods do not automatically get used in regulations. Even when there is an urgent need for regulatory relevant test methods, methods need to pass through a so-called standardization process. This involves following specific agreed processes, which define the timeline and requirements (e.g., validation, documentation, approval) before the method can be integrated in regulatory oriented standards or Test Guidelines from the Organization of Economic Cooperation and Development (OECD). The process is often seen as too complex or too resource (and time) consuming by the scientific community, which inhibits method developers from translating their scientific methods and protocols into standards or OECD Test Guidelines. Numerous incentives exist for scientists to be (more) active in the standardization process and allow regulation to keep up with new scientific developments. These include an increase in research impacts, an expansion and diversification of the international expert network, and an access to more fundings. This paper shows scientists how to reach such outcomes, by providing guidance on how to navigate successfully through the standards and OECD Test Guidelines development processes. Especially the requirements for method validation, which is a prerequisite in this process and common across the different standardization bodies. For further details and insights, readers are invited to consult the various freely available resources generated by the NanoHarmony EU project. These are compiled in the OECD Test Guideline Process Mentor (https://testguideline-development.org/). The active participation of scientists along the entire process toward standards and OECD Test Guidelines is key. Only then can their methods be expanded into a wider, regulatory application toward a safer world.